Fundamental of Entrepreneurship ENT300 : Print Apparel Co. / Aryqqa Syafenne lsmadi ... [et al.] - lsmadi, Aryqqa Syafenne; Karmen, Norsyafiqah; Ismadi, Nur Asyila Syamim; Abdillah, Siti Fatimah; Jos, Syahira (2014)
The name of our company is Print Apparel Co. Our business is in the form of partnership which consists of five members. Each partner contributes certain amount of capitat as agreed in the agreement. The main business activity is to provide services for t-shirt printing, design and embroidery for customers in and around Mukah Town. Our focus is on providing superior quality printed t-shirts and design at a very affordable price. We had agreed that Aryqqa Syafenne binti lsmadi as our General Manager, Syahira binti Jos as the Marketing Manager, Siti Fatimah Abdillah as the Operation Manager, Nur Asyila Syamim binti lsmadi and Norshafiqah Karmen as Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability of the partner. The management team will be led by the General Manager and assist by the other managers.